Bequest of ILAM long playing records (International Library of African Music, 1958)
Through the generosity of Mr. Harry Oppenheimer, who is a Life Member of the African Music Society, a number of Universities and other Institutions have been presented with representative collections of the Library’s recent recordings, where they will be used especially for anthropological, linguistic and musicological studies.
Keywords: African Music